Czy poziom bezrobocia w Polsce zależy od zmian podaży pieniądza? - Więznowski, Artur (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In the article, potential relationship between changes in money supply and unemployment is analyzed. The main thesis is that when there is a monetary shock in the economy, in the short run the labour market is disturbed. Such monetary shocks were observed in Poland and other countries in the last 13 years. When unexpected tightening of monetary policy occurred, then it was always accompanied by the increases in unemployment. However, for the last two or three years another kind of shock appeared. It is very different to earlier ones, because it is the unexpectedly expansionary monetary policy (in respect to changes in main monetary aggregates) which affects the economy. This time it is accompanied by very quick decrease in unemployment and it is hard to say if achieved lover levels of unemployment are sustainable or if they are just a short term reaction to change in monetary policy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 717-727